The Up-Hole Seismic Test Together with the SPT: Description of the System and Method - Pedrini, R. A. A. [UNESP]; Rocha, B. P.; Giacheti, H. L. [UNESP] (Brazilian Soc Soil Mechanics & Geotechnical Engineering, 2018)
A proper geotechnical site characterization has to identify the geometry of relatively homogeneous zones and define indices, strength and stiffness properties of the soils within these zones. The most widely used in situ test to define the stratigraphical profile and to estimate geotechnical parameters is the Standard Penetration Test (SPT). Although it is widely used, this test provides a single index to define a great number of parameters, a peculiar characteristic criticized by many authors. Some authors have shown that it is possible to incorporate the measurement of shear wave velocity (Vs) using the SPT and the up-hole seismic test. This hybrid test can be called the seismic SPT (S-SPT), combining strati-graphic logging, and estimation of geotechnical parameters and determination of shear wave velocity (Vs) values. This paper describes a system to carry out the seismic SPT and the approach to interpret the seismic data. Seismic SPT was carried out at three research sites in the state of Sao Paulo, Brazil to assess its applicability. The Vs values determined by this hybrid test were compared with Vs reference values determined through cross-hole, down-hole and seismic cone penetration tests. The differences between Vs values were, on average, 8.5%, 9.0% and 16.0% for each research site. The hybrid S-SPT test can be used to define the Vs and, consequently G(0) profile, together with the N-value determination.
Keywords: in situ testing; seismic; shear wave velocity; site investigation; SPT; up-hole